Constitutional and Gender Critique of the Implementation of Aceh’s Qanun: Between Sharia Regulations and the Restriction of Women’s Rights - Gandhi Liyorba Indra; Fathul Mu’in (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to provide a constitutional critique of the implementation of qanun in Aceh from the perspectives of the constitution and gender. During its formulation process, the community expressed a desire for Sharia values to be incorporated into the qanun governing the lives of Acehnese people. However, its implementation has the potential to restrict women's rights. This study also seeks to contribute to the reformulation of laws that are fair for all. A qualitative approach is employed in this study, with data collected from library research to analyze constitutional and gender critiques of the implementation of Aceh's qanun. From a constitutional perspective, the study finds that the implementation of Aceh's qanun is not entirely aligned with the national constitution, human rights, and the principles of a unitary state. Although Aceh has special autonomy to implement Islamic law, its enforcement must not contradict the principles of equality before the law, freedom of religion, and the protection of human rights. From a gender perspective, while the qanun aims to uphold Islamic values and establish a well-ordered social structure, its implementation often fails to align with gender justice principles, as it restricts women's rights. To achieve justice for all members of society, it is essential to reassess the application of Aceh’s qanun and ensure women's participation in the decision-making process, so that the resulting policies genuinely reflect the needs and rights of all citizens.